Developing Lectora Inspire-based learning media on social science subjects - Ulfatuzzahara, Trisna (Harmoni Sosial: Jurnal Pendidikan IPS, 2020)
The purpose of this research was: 1.) To analyze the needs of the students to the Lectora inspire learning media; 2.) To produce learning media based on Lectora inspire on; 3.) Made effective the learning media based on Lectora inspire. The type of research is Research and Development (R&D) which refers to the procedural development model that was developed by Borg and Gall, that include research and information collecting, planning, develop a preliminary form of product, preliminary field testing main product revision, main field testing, operational product revision, operational field testing, final product revision, dissemination, and distribution. The result of the research development of learning media based on Lectora Inspire on social science subjects. The result of material expert test or content reached the prevalence level 85%, the design expert of media product reached 87,5%, the learning expert reached 92,5%, the field trial result reached 92,83%. Student learning outcomes on average pretest scores were 56,83, and the posttest score was 83,33. In the standard t-test with a significance level of 0.05 obtained t-count > t-table is 5,09 > 1,699, which means Ho reject and Ha accepted, so there are significant differences between the student before and after using learning media based on Lectora inspire. This showed that developed products had the qualification of high validity level so that the learning media was acceptable in learning.